Pengembangan epistemologi kaum intelektual muslim - Nata, Abuddin (Ta'dibuna: Jurnal Pendidikan Islam, 2023)
The scholars have indeed produced extraordinary works in various fields of religious knowledge based on the Qur'an and Hadith, but rarely do they explicitly explain the epistemological steps taken. As a result, many people have in-depth knowledge of religion and other general knowledge but are unable to develop it or construct new understandings based on the Qur'an and Hadith. This happens because of a lack of understanding of epistemology. As a result, Muslims often only act as consumers, connoisseurs, or adherents of sects, without being able to develop new understandings about various kinds of knowledge. In this study, we use authoritative reference sources and combine bayani (ijtihad) and burhani (observation) methods to explore and demonstrate the methodology of constructing knowledge in Islamic epistemology used by Muslim intellectuals. It is hoped that this effort will encourage the rebirth of the ijtihad movement which produces Muslim intellectuals who are qualified, and credible and provide enlightenment on a local, national, and international scale. Abstrak Para ulama memang telah menghasilkan karya-karya luar biasa dalam berbagai bidang ilmu agama berdasarkan Alquran dan Hadis, namun jarang di antara mereka yang secara eksplisit menjelaskan langkah-langkah epistemologis yang diambil. Akibatnya, banyak orang yang menguasai ilmu agama dan ilmu umum lainnya dengan mendalam, namun tidak mampu mengembangkannya atau mengonstruksi pemahaman baru berdasarkan Alquran dan Hadis. Hal ini terjadi karena kurangnya pemahaman tentang epistemologi. Akibatnya, umat Islam sering hanya berperan sebagai konsumen, penikmat, atau penganut aliran, tanpa mampu mengembangkan pemahaman baru tentang berbagai macam ilmu. Dalam penelitian ini, kami menggunakan sumber rujukan kepustakaan yang otoritatif dan mengombinasikan metode bayani (ijtihad) dan burhani (pengamatan) untuk menggali dan menunjukkan metodologi mengonstruksi ilmu dalam epistemologi Islam yang digunakan oleh kaum intelektual Muslim. Upaya ini diharapkan dapat mendorong lahirnya kembali gerakan ijtihad yang menghasilkan kaum intelektual Muslim yang mumpuni, kredibel, dan memberi pencerahan dalam skala lokal, nasional, maupun internasional.